cos2x+sin²x = 0,75
cos²x - sin²x + sin²x = 0.75
cos²x = 0.75
cosx = ±√0.75 = ±0.5√3
1) cosx = -0.5√3
x₁ = 5π/6 + 2πn
x₂ = -5π/6 + 2πn
n =1 x₁ = (2 + 5/6) π x∉[π; 5π/2]
x₂ = (2- 5/6) π = 7π/6 x∈[π; 5π/2]
n =2 x₁ = (4 + 5/6) π x∉[π; 5π/2]
x₂ = (4- 5/6) π x∉[π; 5π/2]
2) cosx = 0.5√3
x₁ = π/6 + 2πn
x₂ = -π/6 + 2πn
n =1 x₁ = (2 + 1/6) π = 13π/6 x∈[π; 5π/2]
x₂ = (2 - 1/6) π = 11π/6 x∈[π; 5π/2]
n =2 x₁ = (4 + 1/6) π x∉[π; 5π/2]
x₂ = (4- 1/6) π x∉[π; 5π/2]
ответ: x = 7π/6; 11π/6; 13π/6
x + y = 2411,
x + 10y = 6641.
Вычтем из второго уравнения первое,получим 9y = 6641-2411 = 4230.
То есть,y = 470. Тогда, из первого уравнения, x = 1941.